Penggunaan Model Pembelajaran Kooperatif Tipe Number Heads Together untuk Meningkatkan Sikap Percaya Diri dan Hasil Belajar dalam Pembelajaran Pendidikan Kewarganegaraan di Sekolah Dasar - Indani Damayanti; Atim Suparman; Yeye Sukmaya (Jurnal IAI Bunga Bangsa Cirebon, 2020)
This study aims to improve students' self-esteem and student learning outcomes in Civics learning in class IV SDN Inpres Biru students through the Number Head Together type of cooperative learning model. This study uses an action research method using the Kemmis and Mc.Taggart model which consists of four stages. That is : planning, action, observation and reflection which is carried out for two cycles. Data collection techniques using field notes, documentation, observation of teacher activities and observation of student activities, tests and non-tests. The subjects in this study were students of grade IV SDN Inpres Biru. Overall research results have reached or exceeded the research targets set. In cycle 1 the students' self-esteem reached 66.66% and in the second cycle increased 81.6%. Student learning outcomes also experienced a significant increase each cycle. In the first cycle the percentage of students who completed was 59.10% and in the second cycle increased by 87.75%. From the observations in each cycle, students show positive results on Civics learning by applying the NHT model, because this model emphasizes students to provide opportunities for students to share ideas and consider the most appropriate answers. In addition, this technique encourages students to increase the spirit of their collaboration. The implication of this study is the Number Head Together type of cooperative learning model to improve self-confidence and learning outcomes. In the case of village and sub-district government structures. The results of this study indicate an increase in the attitude of confidence and student learning outcomes through the cooperative learning model type Number Head Together. Abstrak Penelitian ini bertujuan untuk meningkatkan sikap percaya diri siswa dan hasil belajar siswa dalam pembelajaran PKn pada siswa kelas IV SDN Inpres Biru melalui model pembelajaran kooperatif tipe Number Head Together. Penelitian ini menggunakan metode penelitian tindakan dengan menggunakan model Kemmis dan Mc.Taggart yang terdiri dari empat tahap yaitu, perencanaan, tindakan, observasi dan refleksi yang dilakukan selama dua siklus. Teknik pengumpulan data menggunakan catatan lapangan, dokumentasi, observasi aktivitas guru dan observasi aktivitas siswa, tes dan non tes. Subyek dalam penelitian ini adalah siswa kelas IV SDN Inpres Biru. Hasil penelitian secara keseluruhan telah mencapai bahkan melebihi target penelitian yang ditetapkan. Pada siklus 1 sikap percaya diri siswa mencapai 66,66% dan pada siklus II mengalami peningkatan yaitu sebanyak 81,6%. Hasil belajar siswa juga mengalami peningkatan yang signifikan setiap siklusnya. Pada siklus I persentase siswa yang tuntas sebesar 59,10% dan pada siklus II mengalami peningkatan sebanyak 87,75%. Dari hasil observasi di setiap siklusnya, siswa menunjukkan hasil yang positif terhadap pembelajaran PKn dengan menerapkan model NHT, karena model ini menitikberatkan kepada siswa untuk memberikan kesempatan kepada siswa untuk saling membagikan ide-ide dan pertimbangan jawaban yang paling tepat. Selain itu tehnik ini mendorong siswa untuk meningkatkan semangat kerjasama mereka. Implikasi dari penelitian ini adalah model pembelajaran kooperatif tipe Number Head Together untuk meningkatkan sikap percaya diri dan hasil belajar. Pada meteri susunan pemerintahan desa dan kecamatan. Hasil penelitian ini menunjukan adanya peningkatan sikap percaya diri dan hasil belajar siswa melalui model pembelajaran kooperatif tipe Number Head Together